Improvement in Performance of ZnO based DSC Prepared by Spraying Method - Winantyo, Rangga; Liyanage, Devinda; Murakami, Kenji (Makara Journal of Technology, 2013)
This paper reports the effect of TiCl4 on the performance of ZnO based DSC. ZnO was used due to its stability against photo-corrosion and photochemical properties similar to TiO2. Thin films of nanocrystalline ZnO were deposited on transparent conducting oxide glass using spray method. The ZnO films were treated using TiCl4. The cell’s efficiency was found to be 2.5% with TiCl4 post-treatment and 1.9% without TiCl4 post-treatment.